New Hermite-Hadamard and Jensen Type Inequalities for h-Convex Functions on Fractal Sets - Vivas, Miguel; Hernández, Jorge; Merentes, Nelson (Revista colombiana de matemáticas, 2017)
Abstract In this paper, some new Jensen and Hermite-Hadamard inequalities for h-convex functions on fractal sets are obtained. Results proved in this paper may stimulate further research in this area.